2009
DOI: 10.1111/j.1365-2672.2009.04279.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of multi-copy strains for optimizing secretory expression of porcine insulin precursor in yeastPichia pastoris

Abstract: Aims:  This study attempted to fully explore the expression potentials of Pichia pastoris for producing porcine insulin precursor (PIP) through PIP copy number optimization. Methods and Results:  Multi‐copy strains were screened employing a highly efficient improved in vivo method and their copy numbers were quantified by real‐time qPCR. A range of Mut+P. pastoris strains harbouring 0, 1, 3, 6, 12, 18, 29, 52 copies of PIP were obtained. After 96 h methanol induction, a bell‐shaped correlation curve was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 34 publications
5
78
1
1
Order By: Relevance
“…These results are comparable with those reported by Zhu et al (2009) [13], where production of a recombinant protein using a methanol-induced vector in P. pastoris increased approximately 10-fold when increasing gene copy number from 1 to 12, but decreased when vectors with higher copy numbers were introduced. In addition Zhu et al, [13] found a reduction in cell growth rate with strains carrying more than the optimal 12 copies of the transgene.…”
Section: Recombinant Protein Expression From P Pastoris Clonessupporting
confidence: 89%
See 4 more Smart Citations
“…These results are comparable with those reported by Zhu et al (2009) [13], where production of a recombinant protein using a methanol-induced vector in P. pastoris increased approximately 10-fold when increasing gene copy number from 1 to 12, but decreased when vectors with higher copy numbers were introduced. In addition Zhu et al, [13] found a reduction in cell growth rate with strains carrying more than the optimal 12 copies of the transgene.…”
Section: Recombinant Protein Expression From P Pastoris Clonessupporting
confidence: 89%
“…In addition Zhu et al, [13] found a reduction in cell growth rate with strains carrying more than the optimal 12 copies of the transgene. In this study a reduction in cell growth rate was noted for SMD1168H cells carrying more than 5 copies of the transgene but this was not observed for X33 cells.…”
Section: Recombinant Protein Expression From P Pastoris Clonesmentioning
confidence: 97%
See 3 more Smart Citations